THE ROLE AND IMPORTANCE OF HISTOLOGY IN NURSING EDUCATION AND PRACTICE - Avezova Nafisa Najmiddinovna; Djumayeva Mastura Axmadovna (Ta’lim innovatsiyasi va integratsiyasi, 2025)
Abstract: Histology, the study of tissues and their microscopic structures, is a foundational discipline in medical and nursing sciences. For nurses, understanding histology enhances their ability to assess and interpret pathological changes, communicate effectively with healthcare teams, and provide evidence-based patient care. This article highlights the significance of histology in the nursing profession, its integration into nursing education, and its applications in clinical practice.